2016
DOI: 10.1128/aem.03061-15
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Spread of Quinolone-Resistant Escherichia coli on Dairy Farms

Abstract: Quinolone-resistant Escherichia coli (QREC) is common in feces from young calves, but the prevalence and genetic diversity of QREC in groups of cattle of other ages and the farm environment are unknown. The aims of the study were to obtain knowledge about the occurrence of QREC on dairy farms, the genetic diversity of QREC within and between farms, and how these relate to the number of purchased animals and geographic distances between farms. We analyzed the within-sample prevalence of QREC in individual fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
(38 reference statements)
0
10
0
1
Order By: Relevance
“…Fluoroquinolone treatment is known to suppress Enterobacteriaceae , but this is followed some days or weeks later by increased prevalence in quinolone resistant Enterobacteriaceae [23]. Another explanation for quinolone resistance could be that quinolone resistant E. coli are common in the feces of pre-weaned dairy calves and the farm environment, hence, calves can acquire exogenous strains from the farm environment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone treatment is known to suppress Enterobacteriaceae , but this is followed some days or weeks later by increased prevalence in quinolone resistant Enterobacteriaceae [23]. Another explanation for quinolone resistance could be that quinolone resistant E. coli are common in the feces of pre-weaned dairy calves and the farm environment, hence, calves can acquire exogenous strains from the farm environment [24].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, few previous studies were carried out to investigate the occurrence and characterization of fluoroquinolone- and quinolone-resistant E. coli in human [7,8]. Quinolone-resistant E. coli has also been detected in healthy cattle and other animals from many other countries [9,10]. Recently, in a study in Bangladesh, quinolone-resistant E. coli was detected from apparently healthy cattle [11].…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish study on dairy farms found that environmental samples (feed and water troughs in calving areas) collected from farms with high levels of quinolone resistant E. coli , showed greater contamination with these organisms than other sample types. Water and feed contamination therefore appeared to play a role in the dissemination of these organisms within the farms (Duse et al., 2016). The frequency of water trough disinfection was negatively correlated with the prevalence of cefotaxime‐resistant bacteria in calves in a study in the US, suggesting transmission of ARB between animals through contaminated drinking water troughs (Markland et al., 2019).…”
Section: Assessmentmentioning
confidence: 99%